Eco-friendly and cost-effective adsorbent derived from blast furnace slag with black liquor waste for hazardous remediation - Naggar, Ahmed Hosny; Dhmees, Abdelghaffar S.; Seaf-Elnasr, Tarek Ahmed; Chong, Kwok Feng; Ali, Gomaa A.M.; Ali, Hazim Mohamed; Kh Alshamery, Rasmih M.; AlNahwa, Lubna H.M.; Bakr, Al-Sayed A (Springerlink, 2024)
The current investigation concerns with preparation eco-friendly and cost-effective adsorbent (mesoporous silica nanoparticles (SBL)) based on black liquor (BL) containing lignin derived from sugarcane bagasse and combining it with sodium silicate derived from blast furnace slag (BFS) for thorium adsorption. Thorium ions were adsorbed from an aqueous solution using the synthesized bio-sorbent (SBL), which was then assessed by X-ray diffraction, BET surface area analysis, scanning electron microscopy with energy dispersive X-ray spectroscopy (EDX), and Fourier transforms infrared spectroscopy (FTIR). Th(IV) sorption properties, including the pH effect, uptake rate, and sorption isotherms across various temperatures were investigated. The maximum sorption capacity of Th(IV) on SBL is 158.88 mg/L at pH value of 4328 K, and 60 min contact time. We demonstrated that the adsorption processes comport well with pseudo-second-order and Langmuir adsorption models considering the kinetics and equilibrium data. According to thermodynamic inspections results, the Th(IV) adsorption process exhibited endothermic and random behavior suggested by positive ΔH° and ΔS° values, while the negative ΔG° values indicated a spontaneous sorption process. The maximum Th(IV) desorption from the loaded SBL (Th/SBL) was carried out at 0.25 M of NaHCO3 and 60 min of contact. Sorption/desorption processes have five successive cycles. Finally, this study suggests that the recycling of BFS and BL can be exploited for the procurement of a promising Th(IV) adsorbents.